Effects of acute hypoxia on the estimation of lactate threshold from ventilatory gas exchange indices during an incremental exercise test - Ozcelik, O; Kelestimur, H (Acad Sciences Czech Republic, Inst Physiology, 2004)
The purpose of this study was to investigate the validity of non-invasive lactate threshold estimation using ventilatory and pulmonary -as exchange indices under condition of acute hypoxia. Seven untrained males (21.4+/-1.2 years) performed two incremental exercise tests using an electromagnetically braked cycle ergometer: one breathing room air and other breathing 12% O-2. The lactate threshold was estimated using the following parameters: increase of ventilatory equivalent for O-2 (V-E/VO2) without increase of ventilatory equivalent for CO2 (V-E/VCO2). It was also determined from the increase in blood lactate and decrease in standard bicarbonate. The V-E/VO2 and lactate increase methods yielded the respective values for lactate threshold: 1.91+/-0.10 l/min (for the V-E/VO2) vs. 1.89+/-0.1 l/min (for the lactate). However, in hypoxic condition, V-E/VO2 started to increase prior to the actual threshold as determined from blood lactate response: 1.67+/-0.1 l/min (for the lactate) vs. 1.37+/-0.09 l/min (for the V-E/VO2) (P=0.0001) i.e. resulted in pseudo-threshold behavior. In conclusion, the ventilatory and gas exchange indices provide an accurate lactate threshold. Although the potential for pseudo-threshold behavior of the standard ventilatory and gas exchange indices of the lactate threshold must be concerned if an incremental test is performed under hypoxic conditions in which carotid body chemosensitivity is increased.
Keywords: exercise; hypoxia; lactate threshold